2016
DOI: 10.1097/ccm.0000000000001742
|View full text |Cite
|
Sign up to set email alerts
|

Liberal Versus Conventional Glucose Targets in Critically Ill Diabetic Patients: An Exploratory Safety Cohort Assessment

Abstract: In a safety cohort of critically ill diabetic patients, a blood glucose concentration target of 10-14 mmol/L resulted in fewer episodes of negative glycemic distance or relative hypoglycemia and reduced insulin administration compared with a target of 6-10 mmol/L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…According to our local unit protocol for diabetic patients [9, 10], intravenous or subcutaneous insulin was administered at a blood glucose level (BGL) above 14 mmol/l targeting a BGL between 10 and 14 mmol/l. Diabetes diagnosis was confirmed by the medical records or by the next-of-kin.…”
Section: Methodsmentioning
confidence: 99%
“…According to our local unit protocol for diabetic patients [9, 10], intravenous or subcutaneous insulin was administered at a blood glucose level (BGL) above 14 mmol/l targeting a BGL between 10 and 14 mmol/l. Diabetes diagnosis was confirmed by the medical records or by the next-of-kin.…”
Section: Methodsmentioning
confidence: 99%
“…However, the liberal strategy significantly reduced (p < 0.01) the measured GV according to the coefficient of variability. (59) In another interesting study recently reported by Di Muzio et al, (60) the researchers performed a prospective analysis of 80 critical patients by applying a conventional strategy (glycemic target: 6-10 mmol/L) or a later liberal strategy (10 - 14mmol/L). Patients subjected to the liberal strategy had a lower relative number of episodes of hypoglycemia as determined by a decrease in blood glucose to below 30% of the premorbid average glycemic value estimated from HbA1c at ICU admission.…”
Section: Introductionmentioning
confidence: 99%
“…Patients subjected to the liberal strategy had a lower relative number of episodes of hypoglycemia as determined by a decrease in blood glucose to below 30% of the premorbid average glycemic value estimated from HbA1c at ICU admission. (60) …”
Section: Introductionmentioning
confidence: 99%
“…Critically ill diabetic patients have a different response to insulin therapy than non-diabetic patients, perhaps due to their relative tolerance to glycemic variability and hyperglycemia (5)(6)(7). The literature has demonstrated that a one-size-fits-all approach to glycemic management is flawed, as surgical patients, cardiac patients, and medical patients have different responses to glucose targets (2,3,8).…”
mentioning
confidence: 99%
“…A study ICU that has short lengths of stay may have a different experience with glucose management than one that has longer lengths of stay. Many patients are managed with subcutaneous insulin and the impact of excluding this group is often lacking from study data collection (7). In short, the methods of patient selection yield an internally valid positive result in a subset of patients, but often are not generalizable to other patient populations.…”
mentioning
confidence: 99%